The death penalty: America's experience with capital punishment - Paternoster, Raymond (Oxford Univ. Press, 2008)
The enduring legacy of capital punishment in the United States -- The legal history and constitutional status of capital punishment in the United States -- Common justifications for the death penalty -- Race, the law, and punishment -- Race and capital punishment -- Problems in administering the death penalty -- Capital punishment in America's future